2019
DOI: 10.1111/tmi.13345
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review: Community‐based programmes with people affected by leprosy

Abstract: objective To analyse community intervention programmes for people affected by leprosy in 'global priority countries'.methods Scoping review of articles in the databases PubMed, Scopus, SciELO, Lilacs and Web of Knowledge that made reference to community intervention programmes aimed at people affected by leprosy in global priority countries and which presented an evaluation of results. Analytical variables analysed were methodological characteristics of the study, type of intervention classified according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Our findings suggest that programs which focus on teaching and supporting regular self-care practice report reduction in cracks, wounds, ulcers and hence potentially disability. However, it is important to reflect on our findings in light of the recent review of Casado et al 21 as well as challenges and opportunities presented by the study, intervention design and reporting standards of included studies. First, comparing our review to that of Casado et al 21 they included 30 papers which covered self-care groups (n = 10), education programs (n = 3), livelihood related community intervention programs (n = 6), stigma reduction programs (n = 6) and interventions related to empowerment (n = 5).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Our findings suggest that programs which focus on teaching and supporting regular self-care practice report reduction in cracks, wounds, ulcers and hence potentially disability. However, it is important to reflect on our findings in light of the recent review of Casado et al 21 as well as challenges and opportunities presented by the study, intervention design and reporting standards of included studies. First, comparing our review to that of Casado et al 21 they included 30 papers which covered self-care groups (n = 10), education programs (n = 3), livelihood related community intervention programs (n = 6), stigma reduction programs (n = 6) and interventions related to empowerment (n = 5).…”
Section: Discussionmentioning
confidence: 93%
“…However, it is important to reflect on our findings in light of the recent review of Casado et al 21 as well as challenges and opportunities presented by the study, intervention design and reporting standards of included studies. First, comparing our review to that of Casado et al 21 they included 30 papers which covered self-care groups (n = 10), education programs (n = 3), livelihood related community intervention programs (n = 6), stigma reduction programs (n = 6) and interventions related to empowerment (n = 5). 21 In our review, we found all 10 of the self-care articles described in the above review, five of which met our inclusion criteria.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations